AN IMPROVED CHANNEL SELECTION ALGORITHM (ICSA) FOR SPECTRUM HAND-OFF IN COGNITIVE RADIO AD HOC NETWORK - M. S. Tekanyi; James A. Orokpo; H. A. Abdulkareem; Tobore O. Alexander (Indonesian Journal of Engineering and Science, 2023)
The exponential growth in wireless communication technology has led to spectrum scarcity. Because of this, the world has moved from Fixed Spectrum Allocation (FSA)  Strategy to Dynamic Spectrum Allocation (DSA) Strategy. Cognitive Radio (CR) is a rapidly growing technique that makes use of DSA, where the licensed users, otherwise known as Primary Users (PUs), share their channel with the unlicensed users, known as Secondary Users (SUs). The SUs can use the PUs channel when they are not being used for transmission, but they have to vacate to another vacant channel when the PUs arrive in their channel. Switching to another vacant channel on the arrival of the PUs to their channels is known as spectrum hand-off. Finding another suitable vacant channel for the SUs to continue their interrupted transmission is challenging. Several researchers have used different techniques to address the challenge of target channel selection for spectrum hand-off by considering channel occupancy alone. Still, they suffer challenges like the high number of spectrum hand-offs, high delay, and low throughput. Therefore, this research focuses on developing an Improved Channel Selection Algorithm (ICSA) that considers channel occupancy serially with signal quality requirements for selecting a particular backup channel for spectrum hand-off. The simulation was carried out using Network Simulator (NS), and the results were plotted using Matlab. The results showed that the ICSA had better performance when compared with the Novel Proactive Hand-off Scheme (NPHS) regarding the number of hand-offs, average delay, and average throughput.